An alternate voltage-controlled current source for electrical impedance tomography applications - Chitturi V.; Farrukh N. (Springer, 2023)
The desirable features of any current source in electrical impedance tomography (EIT) are high output impedance and a constant current for varying loads. Howland current sources are the most popular current sources for EIT applications. Alternately, a simple non-inverting amplifier circuit can be used as a voltage-controlled current source using IC LM7171 op-amp. A constant current of 5 mA (PP) is designed and tested over a wide range of frequencies. The frequency response indicates a stable current up to 1 MHz. These results are validated for an impedance of 1 k? which is usually considered for EIT applications. A buffer circuit is added to this current circuit to meet high output impedance matching. A minor discrepancy is visible between the theoretical value and measured value of the output current due to the tolerance band of the resistors used in the non-inverting amplifier circuit. Springer Nature Singapore Pte Ltd 2019.